Performance Analysis of Data Encryption Algorithms for Secure EHR Transmission - Dudhani, Shraddha M; Lomte, Santosh S (International Journal of Computer Sciences and Engineering, 2019)
Hypothetical Data security is the most troublesome issue on the planet and the diverse security risks in the computerized security must be avoided and to give more prominent protection to the customers additionally, to engage high dependability and openness of the data. For the equivalent the assurance of the proper data encryption estimation depends consistently on its key length, data size and its execution criteria. In this paper, we separated the distinctive data encryption figuring for instance, DES, AES, blowfish, MD5 estimations on the reason of the diverse parameters and made a comparison of these counts for secure trade of EHR.